Thinking, fast and slow / Daniel Kahneman - Kahneman, Daniel, 1934- (New York [etc.] Penguin books, 2012)
This is an important book from an important scholar. Winner (along with his late colleague, Amos Tversky) of the 2002 Nobel Prize in economics--for work on decision making--Kahneman (emer., psychology, Princeton; public affairs, Princeton's Woodrow Wilson School of Public and International Affairs) practically invented the discipline of behavioral economics and more generally transformed the entire approach to the psychology of decision making. This book makes, among many other things, two major contributions. First, Kahneman provides a substantial review and synthesis of the body of research he did with Tversky. Second, he explicates, and organizes the work around, his recent model of ways of thinking: system 1--fast, intuitive, emotional; system 2--slower, more deliberative, logical. Kahneman explores the consequences of this distinction in a variety of domains. Summing Up: Essential. Upper-division undergraduates through faculty and professionals; general readers. R. Levine California State University--Fresno
En portada : The intenational bestseller
Keywords: Psicología cognitiva; Toma de decisión